Metaphor Analysis on “Dungeons and Dragon (Honor among Thieves)” Movie - Hamdani, Haris; Zuriyati; Anwar, Miftakhulkhairah (English Education Study Program Faculty of Teacher Training and Education, 2023)
Language and human are related each other. Some features of language are utilized by people to communicate. There are some features of language, one of them is metaphor. The research aimed at analyzing the use of metaphor in a movie entitled “Dungeons and Dragon (Honor among Thieves)”. The researchers use descriptive qualitative method in conducting the research. The researchers get the data from the movie with length 2 hours 15 minutes and 57 seconds. There are 25 data about metaphor found in Dungeons and Dragon (Honor among Thieves) movie. The metaphors were uttered by the actors on that movie. It was suggested for further research in conducting the research about metaphor with different movies which have more metaphors. Another research was also suggested about analyzing another kind of figurative language combined with metaphor. Keywords: Metaphor, Dungeons and Dragon (Honor among Thieves), Semantic